Faktor-Faktor yang Mempengaruhi Pemilihan Pelembab Tubuh pada Wanita Milenial Muslim di Indonesia - Bonaventura Gema Andika Satria; Clariza Angkawijaya; Jordan Ricky Tanuwijaya; Maulana Alhazmi; Michael Dynatal Haryono (Universitas Prasetiya Mulya, 2019)
This paper aims to deepen literature on choosing preference of body moisturizer among millennials muslim women in Indonesia. There has not been any study that address factors that influence choosing preference of skincare in specific context and in specific country. There are two methods of data collection for this study, through Focus Group Discussion (FGD) and online questionnaire. The research findings suggests that the most important factor preferences are skin suitability, health certificate, and skin allergy. This study would be beneficial for the future of body moisturizer manufacturers in Indonesia to understand the choosing preference of millennials muslim women.